943 Beyond the Adenoma Carcinoma Sequence. (12th October 2021) - Daniel, S; Iype, S
Abstract: Introduction: Looking beyond the adenoma carcinoma sequence researchers have discovered alternate morpho-genetic routes, and tumour biomarkers in colorectal cancer. This has caused a paradigm shift in the management, resulting in improved diagnosis, prevention, and delivery of tailored treatment aiming at specific molecular pathways. Aim: This review summarises pathways beyond the adenoma carcinoma sequence the genetic mechanisms underlying the morphological pathways and their interactions genetics of inherited syndromes and familial non-syndromic colorectal cancers, and the benefits of biomarkers in colorectal cancers. Method: PubMed, Google Scholar, NLM searches based on aims and key words were conducted. Further, academically, and clinically relevant searches were made if more information was required. When required, references of articles were also retrieved. Results: The two main theories regarding the morphological origins of colorectal cancer are the adenoma carcinoma sequence and the De-novo origins. The underlying genetic models are the (i) chromosomal instability pathway (CIN), (ii) the microsatellite instability pathway (MSI) and (iii) the CpG Island methylator phenotype (CIMP) pathways. Though unique, the pathways communicate with each other. The genetic fingerprinting of colorectal cancers has an impact on their tailored management and consequently a through grounding in the basics are essential for those in gastrointestinal subspecialties. Conclusions: Two morphologically distinct pathways and three unique genetic mechanisms have been described. There are significant interactions between them. Behaviours of sporadic and inherited colorectal cancer, their treatment and prognosis depend on our understanding of these mechanisms and the availability of targeted therapies to assist surgical resection.